PENERAPAN MODEL GALLERY WALK DALAM PEMBELAJARAN MENULIS PUISI PADA PESERTA DIDIK KELAS XI SMA NEGERI 1 SURANENGGALA: gallery walk - Nurul Fadhilah Hasyim; Muhammad sholeh, Ade Hasanudin (STKIP Subang, 2025)
This study aims to determine the effectiveness of using the gallery walk model in learning to write poetry for class XI students of SMA Negeri 1 Suranenggala in the 2024/2025 academic year; and describe the learning activities of writing poetry for class XI students of SMA Negeri 1 Suranenggala in the 2024/2025 academic year using the gallery walk model. This study uses an experimental method with a Non-Equivalent Control Group design. The population of this study was all class XI students of SMA Negeri 1 Suranenggala in the 2024/2025 academic year. Using a purposive sampling technique, class XI A was determined as the experimental class with 30 students and class XI C as the control class with 30 students. Research data were collected using data collection techniques in the form of tests and observations. The research instruments were in the form of test and observation instruments. Based on the results of statistical calculations using the two independent t-test (Independent Samples test), the t count was 2.130 and the t table was 2.001. Therefore, tcount (2.130) > ttable (2.001) this shows that H1 is accepted and H0 is rejected. Thus it can be stated that the gallery walk model is effectively applied in learning to write poetry for class XI students of SMA Negeri 1 Suranenggala. Based on the results of the analysis of observational data, it is proven that the application of the gallery walk model can improve writing skills in students and can increase student activity in the process of learning to write poetry for class XI students of SMA Negeri 1 Suranenggala in the 2024/2025 Academic Year. Keywords: Gallery walk, writing poetry, learning.